Análise dos processos de gestão do acesso hospitalar frente à acreditação - Rinaldi, Juliana Ranalli (Universidade Federal de São Carlos, 2019)
Accreditation is a method of evaluation and certification, establishing standards and requirements to promote the quality and safety of care in health institutions. In Brazil, the National Accreditation Organization (ONA) is the responsible for the main accreditation methodology and uses as an evaluation tool the Brazilian Accreditation Manual. This process is voluntary and the main objective is to encourage health services to search, in an organized and systematic way, continuous improvement of its structure, processes and results. This study aimed to analyze the compliance of the procedures related to the subsection "Access management" of the above mentioned manual in relation to ONA’s level 1 accreditation requirements. It is a qualitative research, of descriptive nature of the exploratory type. For this work development, 4 stages have been settled and covered. In step 1 "detailing requirements", a semi-structured questionnaire with 259 items was prepared. In stage 2, "identification of the current situation" visits took place in the areas that have relation with the processes related to Access Management. In step 3, "compliance analysis", the responses for each item verified during the visits in the areas were analyzed, 38.6% (100 questions) of actions taken fulfilled the requirements and 61.4% (159 questions) of taken actions were non-conformities. Finally, in stage 4 "identification and prioritization of systemic nonconformities", a cross-sectional analysis of the most critical nonconformities (NC) in the organization has been performed. A matrix system base regarding Severity, Urgency and Tendency (GUT) has been created to stress the NCs occurrences and for matching the NCs in more than one area. The latter was regarded as systemic NCs. Furthermore, a score table was generated according to the increasing levels in severity from 1 to 5. 124 out of 159 NC items, were NC systemic and they corresponded to 78%, and 35 items were particular NC and corresponded to 22% of the questions. The results found in this research demonstrate that in an evaluation process, the hospital in this study would be deemed as not accredited due having not reached the percentage equal or higher to 70% of conformities, according to ONA’s 2018 manual. The research has made possible a diagnosis of the necessary actions for improvement of work processes related to Access Management, as well as a priority system for the problems in the matrix of severity, urgency and tendency with a ranking to guide the execution of actions. The collecting data instrument, which was elaborated following the details of the subsection requirements, can be used as a tool not only for the institution but also for other organizations that seek to learn the items to be verified in access management. It may also benefit evaluators under ongoing evaluation visits, once the developed instrument takes in account more accurate detail of ONA standard requirement. Finally, the present study has demonstrated the accreditation evaluation process as a helping device for hospitals management in the effort to improve health service practices by standardizing processes and improvement of healthcare programs.
Analysis of hospital access management processes through accreditation
Keywords: Acreditação hospitalar; Admissão do paciente; Alta do paciente; Tecnologia biomédica; Gestão em saúde; Organização e administração; Hospital accreditation; Patient admission; Patient discharge; Biomedical technology; Health management; Organization and administration; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS BIOLOGICAS; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::MEDICINA; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO::GARANTIA DE CONTROLE DE QUALIDADE; OUTROS::ADMINISTRACAO HOSPITALAR; OUTROS::BIOMEDICINA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA